2014
DOI: 10.1074/jbc.m114.560821
|View full text |Cite
|
Sign up to set email alerts
|

ZIP2 Protein, a Zinc Transporter, Is Associated with Keratinocyte Differentiation

Abstract: Background: Few studies have investigated the ZIP proteins specifically expressed in keratinocytes. Results: ZIP2 is highly expressed in differentiating keratinocytes, and their differentiation is inhibited by ZIP2 siRNA. Conclusion: ZIP2 is essential for the differentiation of keratinocytes. Significance: Understanding the regulation of keratinocyte differentiation by zinc and its transporters is crucial for developing new therapies against skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 25 publications
3
61
0
1
Order By: Relevance
“…It is required for differentiation of embryonic skeletal muscle progenitors, for survival of adult skeletal muscle, for promoting myoblast proliferation in mice that were subject to muscle injury, and also for enhancing muscle regeneration in a dystrophic mouse model [26]. ZIP2 is induced by Zn deprivation in monocytes, and is necessary for keratinocyte differentiation [1,27,28]. Experimental evidence suggests a major role in development for ZIP2, as knock-out mice are sensitive to dietary Zn deficiency during pregnancy [29].…”
Section: Introductionmentioning
confidence: 99%
“…It is required for differentiation of embryonic skeletal muscle progenitors, for survival of adult skeletal muscle, for promoting myoblast proliferation in mice that were subject to muscle injury, and also for enhancing muscle regeneration in a dystrophic mouse model [26]. ZIP2 is induced by Zn deprivation in monocytes, and is necessary for keratinocyte differentiation [1,27,28]. Experimental evidence suggests a major role in development for ZIP2, as knock-out mice are sensitive to dietary Zn deficiency during pregnancy [29].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: the inhibition of keratinocyte differentiation upon ZIP2 knock down (Inoue et al 2014); the systemic zinc deficiency caused by enterocyte-specific deletion of ZIP4 (Geiser et al 2012); the zinc-induced acute pancreatitis observed in pancreas-specific ZIP5 knockout mice (Geiser et al 2013); skeletal and connective tissue abnormalities caused by loss of murine ZIP13, which are also observed in human spondylodysplastic Ehlers-Danlos syndrome patients with mutations in ZIP13 (Fukada et al 2008); the deficits in learning and memory seen in mice lacking ZNT3 (Adlard et al 2010); and the loss of zinc-insulin crystals in the pancreatic beta cells of ZNT8 knockout mice (Wijesekara et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The fact that embedded soluble ion-releasing nanoparticles can affect proliferation and migration is not surprising as h-KC migration was previously shown to be affected by the release of iron and zinc ions as specified in the introduction [11], [12], [13], [14], [15], [16]. While KC differentiation, ex vivo, was already described to be induced by topical applications of zinc [16], this parameter has to be studied further in order to supplement the potential effects of our system on the KC behavior.…”
Section: Biological Testingmentioning
confidence: 99%
“…While KC differentiation, ex vivo, was already described to be induced by topical applications of zinc [16], this parameter has to be studied further in order to supplement the potential effects of our system on the KC behavior. While KC rebuild the epidermis and enable the restoration of the homeostasis, FB are recruited on the wound site and proliferate in order to build the granulation tissue.…”
Section: Biological Testingmentioning
confidence: 99%
See 1 more Smart Citation